1985
DOI: 10.1071/ch9851129
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement of Freelingyne with Base

Abstract: Treatment of freelingyne (1) with sodium hydroxide in aqueous methanol gives the rearranged acid (2a).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…This species then undergoes aromatization to form the intermediate (vii), an enantiomer of a brown algal natural product, erogorgiaene. 22,23 Following oxidation of erogorgiaene, the plant natural product 5,8-dihydroxyserrulat-14-en-18-al 24 (viii) is formed. The second stage of the proposed biosynthesis is not well understood; however it may be postulated that the introduction of a nitrogen atom (via an amino acid 25,26 ) results in the ring closure that leads to a quinoline moiety and thus the formation of microthecaline A (1).…”
mentioning
confidence: 99%
“…This species then undergoes aromatization to form the intermediate (vii), an enantiomer of a brown algal natural product, erogorgiaene. 22,23 Following oxidation of erogorgiaene, the plant natural product 5,8-dihydroxyserrulat-14-en-18-al 24 (viii) is formed. The second stage of the proposed biosynthesis is not well understood; however it may be postulated that the introduction of a nitrogen atom (via an amino acid 25,26 ) results in the ring closure that leads to a quinoline moiety and thus the formation of microthecaline A (1).…”
mentioning
confidence: 99%
“…Acylation of ylide 2a with AHPA 1 was performed in Wittig reaction conditions proposed in publications [2,4]. However, we Acid 4 is formed by base-catalysed selfcondensation of AHPA that is well-known in AHPA chemistry [5][6][7][8].…”
Section: Resultsmentioning
confidence: 99%
“…Serrulatenol is the only serrulatane reported which allows access to the 5,8-dioxygenated substitution pattern in contrast with the 7,8 pattern found in the aglycone of the seco-pseudopterosins. The stereochemistry of serrulatenol has been confirmed by X-ray analysis (8). The present problem, which involves conversion of serrulatenol {3} into 5,8-dimethyoxyserrulatane [12], essentially requires deoxygenation at C-13 and C-18 without isomerization at C-11.…”
mentioning
confidence: 85%
“…The serrulatenol used in this study was part of a sample whose structure has been confirmed by Xray crystallography (8).…”
Section: Experimental General Experimentalmentioning
confidence: 99%